Determining the Impact of Adapted Yoga Training on Physical Functioning in Students with Mild Intellectual Disability - Yuvaraj, Dharmalingam; Dibakar, Debnath; Prem, Kumar G.; Aravindh, M.; Ramesh, Aravind J.; Alphi, Georj Saji (Physical Education Theory and Methodology, 2024)
Background. Individuals with mild intellectual disability (ID) often encounter challenges in physical functioning, impacting their overall well-being and quality of life. Traditional exercise programs may not always be accessible or effective for this population due to various barriers. Adapted yoga programs have emerged as a promising alternative, offering tailored interventions to address the unique needs of individuals with ID. Objectives. The study aimed to close this gap by examining the effect of a structured, modified yoga programme on factors related to physical functioning. Materials and methods. A total of 40 students with mild ID, aged between 11 and 15 years, were selected from Special Schools in Coimbatore, Tamil Nadu. A quasi-experimental design was used in this study. The participants were divided into an experimental group undergoing an 8-week adapted yoga program and a control group maintaining regular activities. Physical function parameters were assessed using standardized tests measuring cardiorespiratory endurance, muscular strength and endurance, flexibility, body composition, and balance. The adapted yoga program, conducted by qualified instructors, comprised 8 weeks of sessions, 5 days a week, each lasting 45 to 60 minutes. Statistical analyses confirmed the normal distribution of data and employed paired sample t-tests to assess pre- and post-test differences, with SPSS version 20.0 used for analysis, setting the significance level at 0.05. Results. After undergoing 8 weeks of adapted yoga training, the results showed a significant improvement in the upper body strength (P < 0.04), lower body strength (P < 0.001), core strength (P < 0.002), flexibility (P < 0.00), and static balance (P < 0.00). However, there was no significant difference in body fat and cardiorespiratory endurance between adapted yoga training. Conclusions. This study highlights the potential of adapted yoga programs as an intervention for improving physical functioning in students with mild ID. These findings indicate that the implementation of adapted yoga can be a valuable and accessible intervention for enhancing physical functioning in this population.